Identification of miRNAs as potential modulators of tissue factor expression in patients with systemic lupus erythematosus and antiphospholipid syndrome - TERUEL, R.; PÉREZ‐SÁNCHEZ, C.; CORRAL, J.; HERRANZ, M. T.; PÉREZ‐ANDREU, V.; SAIZ, E.; GARCÍA‐BARBERÁ, N.; MARTÍNEZ‐MARTÍNEZ, I.; ROLDÁN, V.; VICENTE, V.; LÓPEZ‐PEDRERA, C.; MARTÍNEZ, C. (Journal of thrombosis and haemostasis, 2011)
Background: Tissue factor (TF) is the main initiator of the coagulation cascade and elements that may upregulate its expression might provoke thrombotic events. Systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS) are autoimmune diseases characterized by a high TF expression in monocytes. Objectives: To examine the role of microRNAs (miRNAs) in TF expression and to evaluate their levels in SLE and APS patients. Methods: An in silico search was performed to find potential putative binding sites of miRNAs in TF mRNA. In vitro validation was performed transfecting cells expressing TF (THP‐1 and MDA‐MB‐231) with oligonucleotide miRNA precursors and inhibitors. Additionally, reporter assays were performed to test for the binding of miR‐20a to TF mRNA. Levels of miRNAs and TF were measured by quantitative (qRT‐PCR) in patients with APS and SLE. Results: Overexpression of miRNA precursors, but not inhibitors, of two of the members of cluster miR‐17∼92, for example miR‐19b and miR‐20a, in cells expressing TF decreased TF mRNA, protein levels, and procoagulant activity between 30% and 60%. Reporter assays showed that miR‐20a binds to TF mRNA. Finally, we measured levels of miR‐19b and miR‐20a in monocytes from patients with APS and SLE and observed significantly lower miRNAs levels in comparison with healthy subjects inversely correlated with the levels of TF. Conclusions: Down‐regulation of miR‐19b and miR‐20a observed in patients with SLE and APS could contribute to increased TF expression and thus provoke the hypercoagulable state characteristic of these patients.